Tariffs Passing Through Retailers: Do Tariffs Actually Protect Domestic Manufacturers? - Matthew T. Cole; Carsten Eckel (Center for Economic Studies and ifo Institute (CESifo), 2014)
Historically, tariffs have been an attractive policy tool to protect domestic industries. The benefits of such a policy are based on theoretical models that assume foreign manufacturers sell directly to consumers. However, recent empirical evidence suggests that wholesalers and retailers play an active role in international trade. We present a model of retailers that illustrates how accounting for these strategic intermediaries can actually make some domestic manufacturers worse off in response to an increased tariff. Moreover, any production gains that occur are biased towards higher cost domestic manufacturers. This result is not driven by the cannibalization effect of the multiproduct firm literature rather it is the fact that retailers compete over the marginal consumer (the extensive margin).
Keywords: F12; F13; 330; tariffs; retailing; pass-through; protection